Nutritional and food profile of the adult population: an integrative review (Research, Society and Development, 2020)
The consumption of processed and ultra-processed foods is increasing in Latin America, contributing to the increase in overweight and obesity. This paper aims to: investigate and profile the adult Brazilian population. Methodology: an integrative, qualitative and quantitative review study with an exploratory approach. Having as electronic data bases: Google Scholar, Scientific Electronic Library Online (SciELO) and Virtual Health Library (VHL). Following the steps: elaboration of the research question to produce the integrative review; search for primary studies according to predetermined criteria; data extraction: evaluation of included research and analysis of extracted data. The identification of the research question was defined after a search for articles in the literature that reported on the nutritional and food profile of the Brazilian adult population. 12 original articles were selected indexed in the selected databases, in Portuguese, English and Spanish, between the years 2016 and 2020. Conclusion: In view of the data obtained, a high consumption profile of processed, ultra-processed, poor food is evident in fibers, fruits and vegetables, a high-protein, high-fat diet, negatively influencing nutritional status, being overweight and obese, having said that, it is evident that informational measures on nutrition need to be taken to prevent and maintain the Brazilian population.